Interhemispheric parietal cortex connectivity reflects improvement in post-stroke spasticity due to treatment with botulinum toxin-A - Veverka, Tomáš; Hok, Pavel; Trnečková, Markéta; Otruba, Pavel; Zapletalová, Jana; Tüdös, Zbyněk; Lotze, Martin; Kaňovský, Petr; Hluštík, Petr (Journal of the neurological sciences, 2023)
In post-stroke spasticity (PSS), effective treatment with botulinum neurotoxin (BoNT) is associated with transient decrease in activation of the ipsilesional superior parietal lobule (SPL) and intraparietal sulcus (IPS). We hypothesized that this would be reflected in changes in resting-state functional connectivity (rsFC) of the SPL/IPS. Our aim was therefore to assess rsFC of the ipsilesional SPL/IPS in chronic stroke patients with hemiparesis both with and without PSS and to explore the relationship between SPL/IPS rsFC and PSS severity. To this end, fourteen chronic stroke patients with upper limb weakness and PSS (the PSS group) and 8 patients with comparable weakness but no PSS (the control group) underwent clinical evaluation and 3 fMRI examinations, at baseline (W0) and 4 and 11 weeks after BoNT (W4 and W11, respectively). Seed-based rsFC of the atlas-based SPL and IPS was evaluated using a group×time interaction analysis and a correlation analysis with PSS severity (modified Ashworth scale), integrity of the ipsilesional somatosensory afferent pathway (evoked potential N20 latency), and age. In the PSS group, transient improvement in PSS was associated with increase in rsFC between the ipsilesional IPS and the contralesional SPL at W4. The interhemispheric connectivity was negatively correlated with PSS severity at baseline and with PSS improvement at W4. We propose adaptation of the internal forward model as the putative underlying mechanism and discuss its possible association with increased limb use, diminished spastic dystonia, or improved motor performance, as well as its potential contribution to the clinical effects of BoNT.
Keywords: temenní lalok; cévní mozková příhoda; botulotoxiny typu A; Magnetic Resonance Imaging; Muscle Spasticity; Botulinum Toxins, Type A; lidé; Neuromuscular Agents; svalová spasticita; magnetická rezonanční tomografie; Stroke; Parietal Lobe; nervosvalové látky; Humans